Making student motivation the backbone of foreign language education improvement - Wijaya, Henry (LITERA, 2025)
Improving the quality of a foreign language education program, whether through sound educational policy or an effectual change in classroom practices, is not easy. The key to such an endeavor could perhaps be found in paying attention to the student motivation, a factor which is indispensably vital in ensuring the success of any teaching-learning processes, including foreign language. Based on the data of a mixed-method motivation study on university students majoring in foreign language, this academic paper lays out the students' perception of various motivational factors and analyzes what they mean for the initiative to improve a foreign language teaching-learning process. The findings do not only emphasize the utmost importance of constantly and continuously improving the teacher and program quality, but also highlight which areas to focus on. Furthermore, the findings also show that integrative and instrumental motivation should equally influence a program/classroom improvement decision. Lastly, the findings revealed that more motivational aspects should be considered in the currently existing motivation model to further advance the academic theme.